PENGARUH PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK DENGAN VARIABEL INTERVENING KEPUASAN WAJIB PAJAK - Marieta Ariani; Rubiatto Biettant (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2018)
The purpose of this study was to determine the effect of formal taxpayer knowledge and awareness of taxpayers on motor vehicle taxpayer compliance at the SAMSAT POLDA office in West Jakarta. The data used are primary data by distributing questionnaires to Motor vehicle taxpayers registered at the SAMSAT POLDA Office in West Jakarta. The population that will be the object of research is all motorized taxpayers registered at the POLDA SAMSAT office in West Jakarta until the period of December 2017. The sampling technique used is accidental sampling. This study uses the Structural Equation Model method. The results showed that the service of the tax authorities had a positive and significant effect on motor vehicle taxpayer compliance and the satisfaction of taxpayers had a positive and significant effect on motor vehicle taxpayer compliance. The results of this study also concluded that the tax authorities' service had a positive and significant effect on motor vehicle taxpayer compliance through taxpayer satisfaction.